Analysis of innovative technologies and identification of new information tools for effective activities of enterprises on the example of the financial market of Ukraine - Rudyanova, Tatyana; Lebid, Oksana (Technology audit and production reserves, 2021)
The object of research is modern innovative information technologies as a factor in market transformation. The subject of research is the theoretical and methodological foundations of the use of financial technologies in the financial sector of the economy. One of the important problems for the world financial market today is to increase the efficiency of its functioning through the introduction of modern management methods based on innovative information technologies. The most problematic areas is the use of proprietary software. The importance of the latter factor is increasing every year due to the strengthening of legislative requirements and pressure from rightholders. That is why it is advisable to offer the Blueshift platform, which will help expand the capabilities and functions of financial and economic activities. The study used methods of collecting, processing and interpreting information about innovative financial products, and theoretical generalization, analysis of definitions, comparative analysis, concretization and systematization of modern financial technologies, observation and visual presentation of the analysis results. The main hypothesis of the study is the assumption that the use of modern innovative information platforms will allow active users to increase the efficiency of making ready-made decisions when solving problems arising in the financial sector of the economy. It is impossible to confirm this hypothesis without a detailed analysis of financial technologies, as well as innovations associated with modern open source systems, which allow market participants to reduce costs and maximize the likelihood of data protection. In paper, it was proposed to use the Blueshift platform for research and implementation of systematic investment strategies based on its built-in capabilities. The advantages and disadvantages of using the Blueshift platform as a «platform as a service» are analyzed. Thanks to this innovation, such advantages in functionality as information security, ease of adaptation, and economic benefits can be obtained.